A delegacia de defesa da mulher: do tratamento da violência contra a mulher à violência sexual contra crianças e adolescentes - Maia, Jéssica Fernandes (2018)
This dissertation from a research conducted at a Women's' Police station of a city inside the state of São Paulo, where it was looked for to understand the police attendance and the agents' procedure in the police inquiry for when the target of the violence is an adult woman and for when he/she is a child or adolescent, starting from the daily policeman's observation, of interviews with agents and of the analysis of inquiries on sexual violence. During the field work it was observed that the women's great majority assisted at the police station manifested, after the police report, the will of not continuing with the case, same and, above all, in bodily harm occurrences – crime that doesn't depend on the criminal representation to establish the inquiry. In lathe of that fact and, along the observations, it was noticed that a lot of women that manifested a juridical and personal choice different from the one that the police station is capable to offer, they were disqualified of "victim's" category by the agents. It was inferred that the logic of the penal protection backed by the Maria da Penha Law guides the police conduct addressed the assisted people, be adult women or children and adolescents, minimizing the orientation on police procedure and constitutional rights to the adult clientele. Still in field work it was observed that most of the police report and inquiries on crimes against the sexual dignity targeted the violence against children and adolescents. It was also observed a lack of adaptation and preparation in the police procedure for the treatment of sexual crimes against children and adolescents.